Risk Mitigation of Fresh Milk Supply Chain Based on Vulnerability Analysis in Boyolali Regency, Indonesia - Annisa, Warastra Nur; Guritno, Adi Djoko; Sukartiko, Anggoro Cahyo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Fresh milk in Boyolali Regency is currently unable to meet the demand of the processing industry because the quantity is limited and the quality is below the standard. The large number of activities at each tier and the long supply chain flow for fresh milk have the potential to cause a decrease in quality and quantity, making it vulnerable to risk. Therefore, this research aimed to analyze risk management in supply chain and provide mitigation proposals. Data were collected by in-depth interviews with 51 respondents using purposive and snowball sampling techniques. The variables examined include supply chain flow of fresh milk, risks at each tier, causes and impacts of risks, as well as likelihood, severity, and capacity to manage risk. Data processing used ISO 31000:2018 and the Rapid Agricultural Supply Chain Risk Assessment (RapAgRisk) method to assess risk vulnerability. The results showed that in Boyolali Regency, fresh milk supply chain consists of four tiers, namely farmers, as well as milk couriers, collectors, and processors, comprising processing industry and street vendors. Mitigation proposals were given for nine risks in the categories of high, moderate, and low vulnerability. These risks include high animal feed prices, low forage availability, cows being attacked by foot and mouth disease (FMD), adulteration of fresh milk, the amount of fresh milk received by couriers and collectors fluctuating, rejection, sudden demand, and excess stock of fresh milk. Subsequently, risk mitigation proposals were provided to maintain quality and increase fresh milk production.